Games in English language teaching - Vörösmartiné Tőzsér Emma (2003)
In my thesis I will demonstrate some issues related to the role of games in English language teaching, especially the value and usefulness of games. My hypothesis is that games bring teachers and pupils closer together and also help to ease the learning — teaching process. I will show the ways in which the games can be integrated into language teaching as a positive part of the lesson rather than time — fillers. I will prove that the fun and humour elements of the games are important because they create a relaxed atmosphere and help children to communicate. I am interested in other teachers' opinion, and that is why I have done a survey on games. The answers are quite satisfying for me because the result supported my hypothesis. The teachers prefer games because they try to make their lessons more colourful and interesting and they know that games have a very important role in the acquisition of language.